Optimal timing of needle electromyography to diagnose lesion severity in traumatic radial nerve injury. Issue 4 (22nd January 2023) - Steenbeek, Esli D.; Pondaag, Willem; Tannemaat, Martijn R.; Van Zwet, Erik W.; Malessy, Martijn J. A.; Groen, Justus L.
Abstract: Introduction/Aims: In patients with traumatic radial nerve injury (RNI), the chance of spontaneous recovery must be balanced against the benefits of early surgical reconstruction. We aimed to explore the time‐specific value of needle electromyography (NEMG) to diagnose nerve lesion severity. Methods: In this retrospective diagnostic accuracy study at Leiden Nerve Center, patients at least 12 years of age with RNI caused by fractures or fracture treatment were included. The sensitivity and specificity of the patients' first NEMG examination were assessed, stratified by the timing after the nerve injury. The absence of motor unit potentials (MUPs) in muscles distal to the nerve lesion was considered a positive test result. Lesion severity was dichotomized to moderate injury (spontaneous Medical Research Council grade ≥3 recovery) or severe injury (poor spontaneous recovery or surgical confirmation of a mainly neurotmetic lesion). Results: Ninety‐five patients were included in our study. The sensitivity of NEMG to detect severe RNI was 75.0% (3 of 4) in the fourth, 66.7% (2 of 3) in the fifth, and 66.7% (2 of 3) in the sixth month after the nerve injury. The specificity in the first to the sixth month was 0.0% (0 of 1), 50.0% (2 of 4), 77.3% (17 of 22), 95.5% (21 of 22), 95.8% (23 of 24), and 100.0% (12 of 12), respectively. Discussion: The specificity of NEMG is higher than 95% and therefore clinically relevant from the fourth month after the nerve injury onward. Absence of MUPs at this time can be considered an indication to plan nerve exploration. Moreover, the presence of MUPs on NEMG does not completely exclude the necessity for surgical reconstruction. Abstract : Time‐dependent specificity of needle electromyography for severe vs moderate lesions in patients with radial nerve injury caused by fractures or fracture treatment, with 95% confidence intervals. From the fourth month after the nerve injury onward, specificity was more than 95%. A positive test result (ie, absence of motor unit potentials in muscles distal to the nerve lesion) at this time can be considered an indication to plan surgical nerve exploration.